A high-strength anti-sewage gel coating and its preparation method and application
By using ultraviolet light-induced polymerization technology of water-soluble monomers, zwitterionic monomers and crosslinking agents in marine antifouling coatings, the problem of insufficient antifouling capacity of existing coatings under static conditions is solved, and high-intensity, low-cost antifouling and drag reduction effects are achieved.
Patent Information
- Application Number
- CN202310901812.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-07-21
AI Technical Summary
The existing marine antifouling coatings have insufficient antifouling capacity under static conditions and are expensive, so the adhesion between the coating and the substrate needs to be further improved.
Water-soluble monomers, zwitterionic monomers and crosslinking agents (such as nano-aluminum hydroxide, trehalose or vapor-phase silica) are used as raw materials to induce polymerization by ultraviolet light on the surface of the matrix material to form a high-intensity anti-water gel coating.
The prepared high-strength anti-sewage gel coating has excellent mechanical properties, antibacterial and protein-resistant effects and drag-reducing properties, and has a simple process, easy raw materials and low cost.
Smart Images

Figure CN116921180B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogels, and in particular relates to a high-strength anti-sewage gel coating and a preparation method and application thereof. Background Art
[0002] Ships, submarines, offshore drilling facilities, etc. are common marine transportation and exploration equipment. When these equipment are in contact with seawater for a long time, a large number of marine organisms tend to attach to them, increasing the roughness of the hull surface and fuel loss, accelerating hull corrosion, and shortening the service life. This phenomenon is called marine biofouling. According to incomplete statistics, the economic losses caused by marine biofouling exceed hundreds of billions of dollars each year. Therefore, studying marine anti-fouling issues and reducing the attachment of marine organisms to ships and other offshore equipment is of great significance to the development of the marine industry.
[0003] There are two main antifouling strategies for marine antifouling coatings: one is chemically active coatings that use toxicity and release fungicides to kill attached marine organisms; the other is non-toxic coatings that prevent marine organisms from attaching to the hull surface through non-chemical reactions. The first type of coating is mainly coatings containing tributyltin or cuprous oxide, but studies have found that these chemicals will accumulate in seawater while killing attached organisms, causing mutations and deformities in marine organisms, and even endangering human life and health through the food chain.
[0004] Antifouling coatings from the perspective of preventing marine organisms from attaching mainly include conductive polymer antifouling coatings, self-polishing antifouling coatings with soluble silicates as antifouling agents, low surface energy silicone, fluorocarbon coatings, etc. For example, the Chinese patent document with publication number CN102732106A discloses an antifouling coating for marine structures, which is prepared from 24 to 35 fluorocarbon resins, 30 to 40 micron tourmaline powder modified by fluorine-containing polymers, and 20 to 30 nano titanium dioxide powder modified by fluorine-containing polymers; the Chinese patent document with publication number CN105062248A discloses a cationic antifouling and drag-reducing composite functional coating and coating, which is prepared from granular cationic fillers, film-forming resins, curing agents and diluents. The granular cationic filler is a microparticle with a positive charge on the surface; the Chinese patent document with publication number CN113773436A discloses an amphiphilic silicone coating, which obtains a hydrophilic terminal compound by the reaction of thioglycerol, butyl acrylate and N-vinyl pyrrolidone; the hydrophilic terminal compound is introduced into the main chain as a side chain to form a comb-like structure, and an amphiphilic silicone coating is synthesized through a condensation reaction. The silicone coating has excellent mechanical strength, low surface energy, and is not conducive to the attachment of marine organisms.
[0005] However, under static conditions, the lack of shear force provided by water flow makes the silicone coating have insufficient antifouling ability, while fluorocarbon coatings and conductive polymer antifouling coatings are expensive, and the adhesion between the coating and the substrate needs to be further improved. Therefore, it is necessary to provide a hydrogel coating with easy-to-obtain raw materials, simple process, and dual functions of antifouling and drag reduction. Summary of the invention
[0006] The invention provides a method for preparing a high-strength anti-sewage gel coating, with mild reaction conditions and simple and easy process. The prepared high-strength anti-sewage gel coating has the dual functions of anti-fouling and drag reduction, and has strong bonding with a base material.
[0007] The specific technical solutions adopted are as follows:
[0008] A method for preparing a high-strength anti-sewage gel coating comprises the following steps:
[0009] (1) soaking the substrate material in a first solution for pretreatment, taking it out and drying it to obtain a pretreated substrate material; the solvent of the first solution includes acetone, and the solute includes polyvinyl acetate and an initiator;
[0010] (2) Using water-soluble monomers, zwitterionic monomers and crosslinking agents as raw materials, ultraviolet light-induced polymerization occurs on the surface of the pretreated substrate material to obtain the high-strength anti-sewage gel coating; the crosslinking agent is at least one of nano aluminum hydroxide, trehalose and fumed silica.
[0011] The present invention uses a mixed solution of initiator, polyvinyl acetate and acetone to treat the surface of different substrate materials, so that a primer layer with an initiator is formed on the surface of the substrate material; the hydrogel molecular chains are all initiated by the initiator on the surface of the substrate material, and polyvinyl acetate itself has an adhesion effect, thereby achieving the purpose of strong bonding; the crosslinking agent (nano aluminum hydroxide, trehalose or gas phase silica) forms physical crosslinking points through coordination bonds or hydrogen bonds, so that the hydrogel has excellent mechanical properties. The introduction of zwitterionic monomers in the hydrogel can strongly adsorb a layer of water molecules on the surface of the hydrogel coating through ion hydration, thereby forming a fixed water layer. According to the volume exclusion principle, the water layer can effectively inhibit the attachment of microorganisms in the ocean and play a role in anti-fouling and drag reduction; in addition, by selecting two monomers with polyelectrolyte effect and anti-polyelectrolyte effect, the swelling degree of the hydrogel coating of the present invention in water and salt water does not change much, thereby ensuring that the coating will not fall off from the substrate surface due to changes in swelling degree.
[0012] The substrate material includes but is not limited to glass, metal, rubber, plastic, polyurethane sheet and the like.
[0013] Preferably, in step (1), the immersion time is 0.2 to 10 hours, and the immersion-removal process is repeated 2 to 3 times, which is conducive to sufficient pretreatment.
[0014] The initiator is a water-soluble photoinitiator, including 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxy-cyclohexyl-phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,2'-azobisisobutylamidine dihydrochloride or 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.
[0015] Preferably, in the first solution, the mass ratio of polyvinyl acetate, initiator and acetone is 0.5-5.0: 0.5-5.0: 100. Under this ratio, the amount of polyvinyl acetate is sufficient to make the initiator firmly adhere to the surface of the substrate material, and the amount of initiator is sufficient to completely initiate all monomers.
[0016] The water-soluble monomer is an acrylic monomer, including acrylic acid or acrylic acid derivatives.
[0017] The zwitterionic monomer is at least one of the compounds having structural formulas (I) to (IV);
[0018]
[0019] Among them, R 1 is H or methyl; R 2 and R 3 Independently selected from H or C 1 ~C 5 Aliphatic hydrocarbon group; n is an integer of 1 to 3; Z 1 is a benzenesulfonic acid group, a sulfonic acid group, a phosphoric acid group, a benzenesulfonate group, a sulfonate group or a phosphate group; X is H, an alkali metal or an ammonium group; and the structural formula of Y is any one of the following formulae:
[0020]
[0021] Among them, R 4 and R 7 Independently selected from C 2 ~C 5 Aliphatic hydrocarbon group, R 5 , R 6 , R 8 and R 9 Independently selected from C 1 ~C 5 Aliphatic hydrocarbon group, R 10 C 1 ~C 5 Aliphatic hydrocarbon or phenyl, J is N or P, Z 2It is a halogen, a sulfonic acid group, a sulfate ester group, a phosphite group, a monophosphoric acid group or an acetate group.
[0022] Preferably, the zwitterionic monomer is 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 3-[N,N-diethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]ethane-1-carboxylic acid inner salt, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-phosphate inner salt or 3-[N,N-diethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]ethane-1-carboxylic acid inner salt.
[0023] The zwitterionic monomer structure contains both an olefinic bond part and a betaine side group part, so that it has both polymerization activity and electrical neutrality. In the betaine-type polymer formed by further polymerization, the anionic and cationic groups are located on the side groups of the same monomer unit on the same macromolecular chain. The side chain combines with water molecules through ion solvation to form a dense water layer on the surface, showing good anti-protein adsorption ability. The dense water layer is the key to anti-protein adsorption.
[0024] In the cross-linking agent, the particle size of nano aluminum hydroxide is 10-50nm, and the particle size of fumed silicon dioxide is 30-100nm.
[0025] Preferably, the mass ratio of the water-soluble monomer, the zwitterionic monomer and the crosslinking agent is 0.8-8.0: 0.8-8.0: 1. The hydrogel prepared under this ratio has a lower swelling degree and excellent mechanical properties.
[0026] Preferably, in step (2), a water-soluble monomer, a zwitterionic monomer and a cross-linking agent are dissolved in water to obtain a precursor solution; the pretreated matrix material is then placed in a mold, the precursor solution is injected into the mold, and ultraviolet light is cross-linked and cured at room temperature for 0.5-3 hours to obtain the high-strength anti-sewage gel coating.
[0027] The invention also provides a high-strength anti-sewage gel coating prepared by the preparation method of the high-strength anti-sewage gel coating.
[0028] The present invention also provides application of the high-strength anti-fouling gel coating in the field of marine antifouling.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The high-strength anti-sewage gel coating provided by the present invention has good mechanical properties, with a maximum tensile strength of 1.7 MPa and an elongation at break of 3500-3700%.
[0031] (2) The high-strength anti-sewage gel coating provided by the present invention has excellent antibacterial and anti-protein effects, and can reduce the friction of the base material by 40 to 90%, with obvious drag reduction effect.
[0032] (3) The high-strength anti-sewage gel coating provided by the present invention has little swelling degree in water and salt water, and has high bonding strength and is not easy to fall off from the surface of the base material.
[0033] (4) The preparation method provided by the present invention can be operated at room temperature, the process is simple and easy, the raw materials are easily available and the cost is low, and it is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a fluorescence microscope photograph of the substrate material coated with the high-strength anti-sewage gel coating in Example 1, which adsorbs Staphylococcus aureus.
[0035] Figure 2 This is a fluorescence microscope photograph of the substrate material coated with the high-strength anti-sewage gel coating in Example 1, which shows the adsorption of Escherichia coli.
[0036] Figure 3 This is a fluorescence microscope photograph of the substrate material coated with the high-strength anti-sewage gel coating in Example 3, which shows the adsorption of Staphylococcus aureus.
[0037] Figure 4 This is a fluorescence microscope photograph of the substrate material coated with the high-strength anti-sewage gel coating in Example 3, which shows the adsorption of Escherichia coli. DETAILED DESCRIPTION
[0038] The present invention is further illustrated below in conjunction with the examples and accompanying drawings. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0039] In the embodiment, the particle size of the nano aluminum hydroxide used is 10-50 nm, the particle size of the fumed silica is 30-100 nm, and the density of 20 wt % nano aluminum hydroxide aqueous dispersion and 20 wt % fumed silica aqueous dispersion are both about 1 g / mL.
[0040] Example 1
[0041] Polyvinyl acetate, photoinitiator 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) and acetone are prepared into a first solution at a mass ratio of 1:1:100, and a glass plate is immersed in the first solution for 0.5 h, then taken out and dried, and the above operation is repeated twice to obtain a pretreated matrix material;
[0042] The pretreated glass plate is placed in a mold; 3.459 g of acrylic acid, 3.352 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 10 mL of 20 wt% nano aluminum hydroxide aqueous dispersion are weighed and added into 10 mL of deionized water, and after being mixed evenly, the solution is injected into the mold, and irradiated under a 365 nm ultraviolet lamp for 2 hours to obtain the high-strength anti-sewage gel coating.
[0043] Example 2
[0044] A first solution is prepared with polyvinyl acetate, photoinitiator 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) and acetone in a mass ratio of 2:1:100, and a glass plate is immersed in the first solution for 1 hour, then taken out and dried, and the above operation is repeated twice to obtain a pretreated substrate material;
[0045] The pretreated glass plate is placed in a mold; 7.406 g of methacrylic acid, 2.011 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 10 mL of 20 wt% nano aluminum hydroxide aqueous dispersion are weighed and added into 10 mL of deionized water, and after being mixed evenly, the solution is injected into the mold, and irradiated under a 365 nm ultraviolet lamp for 2 hours to obtain the high-strength anti-sewage gel coating.
[0046] Example 3
[0047] A first solution is prepared with polyvinyl acetate, photoinitiator 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) and acetone in a mass ratio of 1:2:100, and a plastic plate is immersed in the first solution for 0.5 h, then taken out and dried. The above operation is repeated twice to obtain a pretreated substrate material;
[0048] The pretreated plastic plate is placed in a mold; 4.937 g of acrylic acid, 3.352 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 2 g of trehalose, and 5 mL of 20 wt% nano aluminum hydroxide aqueous dispersion are weighed and added into 10 mL of deionized water, and after being mixed evenly, the solution is injected into the mold, and irradiated under a 365 nm ultraviolet lamp for 0.5 h to obtain the high-strength anti-sewage gel coating.
[0049] Example 4
[0050] A first solution is prepared with polyvinyl acetate, photoinitiator 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) and acetone in a mass ratio of 3:3:100, and a glass plate is immersed in the first solution for 5 hours, then taken out and dried, and the above operation is repeated twice to obtain a pretreated substrate material;
[0051] The pretreated glass plate is placed in a mold; 3.805 g of acrylic acid, 3.821 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 2.5 mL of 20 wt% nano aluminum hydroxide aqueous dispersion are weighed and added into 17.5 mL of deionized water, and after being mixed evenly, the solution is injected into the mold, and irradiated under a 365 nm ultraviolet lamp for 1 hour to obtain the high-strength anti-sewage gel coating.
[0052] Example 5
[0053] A first solution is prepared with polyvinyl acetate, photoinitiator 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) and acetone in a mass ratio of 2:2:100, and the rubber sheet is immersed in the first solution for 2 hours, then taken out and dried, and the above operation is repeated twice to obtain a pretreated base material;
[0054] The pretreated rubber plate is placed in a mold; 2.162 g of acrylic acid, 8.380 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 10 mL of 20 wt% nano aluminum hydroxide aqueous dispersion are weighed and added into 10 mL of deionized water, and after being mixed evenly, the solution is injected into the mold, and irradiated under a 365 nm ultraviolet lamp for 1.5 hours to obtain the high-strength anti-sewage gel coating.
[0055] Example 6
[0056] A first solution was prepared with polyvinyl acetate, photoinitiator 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) and acetone in a mass ratio of 1:3:100, and a stainless steel plate was immersed in the first solution for 1.5 hours, taken out and dried, and the above operation was repeated twice to obtain a pretreated substrate material;
[0057] The pretreated stainless steel plate is placed in a mold; 6.247 g of hydroxyethyl methacrylate (HEMA), 5.028 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 7.5 mL of 20 wt% nano aluminum hydroxide aqueous dispersion are weighed and added into 12.5 mL of deionized water, and after being mixed evenly, the solution is injected into the mold, and irradiated under a 365 nm ultraviolet lamp for 2 hours to obtain the high-strength anti-sewage gel coating.
[0058] Example 7
[0059] A first solution was prepared with polyvinyl acetate, photoinitiator 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) and acetone in a mass ratio of 3:1:100, and a glass plate was immersed in the first solution for 3 hours, then taken out and dried. The above operation was repeated three times to obtain a pretreated substrate material;
[0060] The pretreated glass plate is placed in a mold; 7.264 g of acrylic acid, 3.352 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 4 g of trehalose are weighed and dissolved in 20 mL of deionized water, and after mixing evenly, the solution is injected into the mold and irradiated under a 365 nm ultraviolet lamp for 2 hours to obtain the high-strength anti-sewage gel coating.
[0061] Example 8
[0062] A first solution is prepared with polyvinyl acetate, photoinitiator 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) and acetone in a mass ratio of 2.5:1:100, and a polyurethane sheet is immersed in the first solution for 2.5 hours, taken out and dried, and the above operation is repeated twice to obtain a pretreated matrix material;
[0063] The pretreated polyurethane sheet is placed in a mold; 3.412 g of acrylamide (AM), 6.704 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 10 mL of 20 wt% fumed silica aqueous dispersion are weighed and added into 10 mL of deionized water, and after mixing evenly, the solution is injected into the mold, and irradiated under a 365 nm ultraviolet lamp for 2 hours to obtain the high-strength anti-sewage gel coating.
[0064] Example 9
[0065] A first solution is prepared with polyvinyl acetate, photoinitiator 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone) and acetone in a mass ratio of 2:3:100, and a polyurethane sheet is immersed in the first solution for 4 hours, then taken out and dried. The above operation is repeated twice to obtain a pretreated matrix material;
[0066] The pretreated polyurethane sheet is placed in a mold; 2.880 g of acrylic acid, 0.925 g of N,N-dimethylacrylamide (DMAA), 5.587 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 8 mL of 20 wt% fumed silica aqueous dispersion are weighed and dissolved in 12 mL of deionized water, and after being mixed evenly, the solution is injected into the mold, and irradiated under a 365 nm ultraviolet lamp for 4 hours to obtain the high-strength anti-sewage gel coating.
[0067] Comparative Example 1
[0068] A glass plate that has not been pretreated is placed in a mold; 3.459 g of acrylic acid, 3.352 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 1 g of chemical cross-linking agent N,N-methylenebisacrylamide are weighed and added to 18 mL of deionized water. After mixing evenly, the solution is injected into the mold and irradiated under a 365 nm ultraviolet lamp for 2 hours. The obtained hydrogel coating has poor mechanical properties and cannot be bonded to the surface of the substrate material.
[0069] Sample analysis
[0070] The thickness of the high-strength anti-sewage gel coating and its thickness after swelling equilibrium, mechanical properties, friction force and antibacterial and anti-protein effects were tested using the following methods:
[0071] Mechanical property test: The hydrogel samples were cut into dumbbell shapes with a cutter and subjected to a tensile test on a tensile machine (Instron, 5543A).
[0072] Friction test: The sample was bonded to the fixture (flat plate, 20 mm in diameter) of an AR-G2 rheometer (TA Instruments, USA). The normal stress was kept at 1 N, and the test was performed under set shear rate, temperature and other conditions.
[0073] Anti-protein adsorption test: prepare phosphate buffer solution (PBS, concentration of 10mmol / L, pH=7.4, I=150mmol / L), prepare a series of concentrations of bovine serum albumin (BSA) with PBS solution, and test it with Bradford method through UV spectrometer (Varian / cary50), and obtain the relationship curve between the characteristic UV absorption peak intensity and solution concentration (Note: The characteristic UV absorption peak of BSA is located at about 277nm, and the special UV absorption peak after labeling with Coomassie Brilliant Blue dye is at about 595nm); then soak the test samples in PBS solution with a concentration of 1g / L BSA, and keep them in a constant temperature oscillation environment (oscillation frequency: 150rpm, temperature: 37℃, time: 24h). The protein adsorption amount on the sample surface is characterized by the change in the intensity of the characteristic UV absorption peak of the test sample before and after soaking in the protein solution.
[0074] Anti-bacterial adhesion test: The experiment selected Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) as representatives, and the hydrogel samples were immersed in the culture solution of the two bacteria. After a period of time, the bacterial adhesion on the hydrogel surface was observed. Each sample was coated on three substrates as parallel samples, and the fluorescence photos were obtained under a fluorescence microscope (ThermoFisher Scientific, EVOS FL Auto 2) with a magnification of 100 times.
[0075] SEM observation: Prepare suspensions of Escherichia coli and Staphylococcus aureus with PBS solution at a concentration of 108 cells / mL, place the soft coating that has reached swelling equilibrium in the PBS solution into the above bacterial solution, and place it in a constant temperature oscillation environment (oscillation frequency: 100 rpm, temperature: 37°C, time: 3h), then take out the soft coating, gently rinse it with PBS solution 2-3 times, and soak it in 2.5wt% glutaraldehyde PBS solution for cross-linking and fixation of bacteria (temperature: 4°C, time: 4h). Then dehydrate the soft coating with ethanol aqueous solutions with volume fractions of 30%, 50%, 70%, 80%, 90%, and 100%, freeze-dry, and perform SEM testing (S-4800).
[0076] Table 1 Performance test results of medium and high strength anti-sewage gel coatings in Examples 1-9
[0077]
[0078] The results in Table 1 show that the high-strength anti-sewage gel coating prepared by the method of the present invention has good mechanical properties, a tensile strength of up to 1.7 MPa, an elongation at break of up to 3500-3700%, and a small degree of swelling. The friction of the substrate material coated with the high-strength anti-sewage gel coating is reduced by 40%-90%, and the drag reduction effect is obvious; and the high-strength anti-sewage gel coating has very low adsorption of bovine serum albumin, Escherichia coli and Staphylococcus aureus, such as Figure 1-Figure 4 As shown, it has excellent antibacterial and anti-protein effects.
[0079] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-strength anti-sewage gel coating, characterized in that: The following steps are involved: (1) soaking the substrate material in a first solution for pretreatment, taking it out and drying it to obtain the pretreated substrate material; the solvent of the first solution is acetone, and the solute is polyvinyl acetate and an initiator; the initiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone; in the first solution, the mass ratio of polyvinyl acetate, initiator and acetone is 0.5-5.0:0.5-5.0:100; (2) dissolving a water-soluble monomer, a zwitterionic monomer and a cross-linking agent in water, and using the water-soluble monomer, the zwitterionic monomer and the cross-linking agent as raw materials to initiate ultraviolet polymerization on the surface of the pretreated substrate material to obtain the high-strength anti-sewage gel coating; the cross-linking agent is at least one of nano aluminum hydroxide, trehalose, and fumed silica; the water-soluble monomer is acrylic acid, methacrylic acid or acrylamide; the mass ratio of the water-soluble monomer, the zwitterionic monomer and the cross-linking agent is 0.8-8.0:0.8-8.0:1; The zwitterionic monomer is 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt.
2. The method for preparing the high-strength anti-sewage gel coating according to claim 1, characterized in that: In step (1), the soaking time is 0.2 to 10 h, and the soaking-removal process is repeated 2 to 3 times.
3. The method for preparing the high-strength anti-sewage gel coating according to claim 1, characterized in that: In the cross-linking agent, the particle size of nano aluminum hydroxide is 10-50 nm, and the particle size of fumed silicon dioxide is 30-100 nm.
4. A high-strength anti-sewage gel coating prepared according to the preparation method of the high-strength anti-sewage gel coating according to any one of claims 1 to 3.
5. Application of the high-strength anti-fouling gel coating according to claim 4 in the field of marine antifouling.
Citation Information
Patent Citations
Antifouling coating composition for marine structures, coating preparation method and obtained coating
CN102732106A
Cationic type antifouling and anti-drag composite functional paint and coating
CN105062248A
Amphiphilic organic silicon coating, preparation method and application thereof
CN113773436A
Preparation method and application of high-strength, anti-fouling and anti-drag soft hydrogel coating
CN108727937A
Method for simple and rapid preparation of hydrogel bilayer film with high adhesion acting force
CN109021166A